Família no contexto pós-moderno: como utilizar referenciais teóricos da sociologia e da filosofia contemporâneas à luz da teologia - Oliveira, Roberto Marcelino de (2011)
The family is a fundamental unit in the constitution of the human personality that over centuries has undergone transformations. Pastoral counseling is visible in the tragedies of the families in postmodern society. We read from the introductory family law, sociology and anthropology as a tool in understanding the family and, above all, how can we use them in line with the advice. In Catholic theology there is a look from the Vatican with its biblical and pastoral collaboration in the field of family . Finally, we point out pertinent points for guidance in pastoral counseling in family life in postmodern society.